THE INFLUENCE OFWORD OF MOUTH, BRAND IMAGE, AND PRODUCT ATTRIBUTES ON BLACKBERRY PRODUCT PURCHASING DECISIONS. - Arni Saraswati; Sri Suryoko; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2016)
Research it is based on a decrease in the sale of blackberry in the last three years. Many factors that must be considered in the decision to buy a product for consideration in decision making. The purpose of this research is: to analyze the influence of word of mouth , brand image, and product attributes on Blackberry product purchasing decisions. This type of research is explanatory type . In this study will explain the influence between the variables to test the hypothesis . The population in this study were all students Fisip Undip . Sampling technique using purposive sampling , namely Fisip Undip student who uses a Blackberry mobile phones . The sampling technique using the formula lameshow, so the sample amounted to 96 respondents . The results showed that word of mouth , brand image and product attributes have a positive and significant influence on purchasing decisions Blackberry products . This is evidenced by test F statistics that indicate 119,559 F count > F table 2,70. The advice given is a Blackberry product companies must constantly innovate by adding features products that are more practical , effective , and expressive .